Influence of the Sodium Titanate Crystal Size of Biomimetic Dental Implants on Osteoblastic Behavior: An In Vitro Study - Saray Fernández-Hernández; Javier Gil; Daniel Robles-Cantero; Esteban Pérez-Pevida; Mariano Herrero-Climent; Aritza Brizuela-Velasco (Biomimetics)
Treating the surfaces of dental implants in an alkaline medium allows us to obtain microstructures of sodium titanate crystals that favor the appearance of apatite in the physiological environment, producing osteoconductive surfaces. In this research, 385 discs made of titanium used in dental implants underwent different NaOH treatments with a 6M concentration at 600 °C and cooling rates of 20, 50, 75, and 115 °C/h. Using high-resolution electron microscopy, the microstructures were observed, and the different crystal sizes were determined and compared with control samples (those without biomimetic treatment). Roughness, wettability, surface energy and the sodium content of the surface were determined. The different surfaces were cultured with human osteoblastic cells; cell adhesion was determined at 3 and 14 days, and the degree of mineralization was determined at 14 days via alkaline phosphatase levels. Variations in the microstructure and size of sodium titanate crystals in NaOH solutions rich (1 g/L) or low in calcium (approximately 100 ppm) were determined. The results show that as the cooling rate increases, the size of the crystals decreases (from 0.4 μm to 0.8 μm) except for the case of 115 °C/h, when the rate is too fast for crystalline nucleation to occur on the surface of the titanium. The thermochemical treatment does not influence the roughness or the cooling rate since a Sa of 0.21 μm is maintained. However, the presence of titanate causes a decrease in the contact angle from 70° to 42° and, in turn, causes an increase in the total surface energy from 35 to 49.5 mJ/m2, with the polar component standing out in this energy increase. No variations were observed in the thermochemical treatments in the presence of sodium, which was around 1200 ppm. It was observed that as the size of the crystals decreases, cell adhesion increases at 3 days and decreases at 14 days. This is because finer crystals on the surface are already in the mineralization process, as demonstrated using the level of alkaline phosphatase that is maximal for the cooling rate of 75 °C/h. It was possible to confirm that the variations in the concentrated NaOH solutions with different calcium contents did not affect the crystal sizes or the microstructure of the surface. This research makes it possible to obtain dental implants with different mineralization speeds depending on the cooling rate applied.